PENGENALAN PERAN SISTEM OPERASI DALAM MENJALANKAN PROGRAM APLIKASI PADA KOMPUTER DAN SMARTPHONE DI MTS ISLAMIYAH WONGSOREJO - Zaehol Fatah; Mita Abelia (Jurnal Padamu Negeri, 2026)
Operating system introduction activities are important efforts to improve students' understanding of information technology, especially in the use of personal computers and smartphones. This study aims to examine the role of operating systems in running application programs and increase students' insight at MTs Islamiyah Wongsorejo. The method used is a qualitative descriptive approach with literature study techniques and observations during the seminar. The results of the activity indicate that the operating system has a fundamental role that acts as a connecting medium between hardware and software systems, as well as managing system resources that enable applications to run optimally. In addition, there are differences in the implementation of operating systems on personal computers and smartphones, but both still have the same basic principles. The implementation of the seminar also showed an increase in participant participation and understanding, which was marked by active participation in discussions and the ability to re-explain the material presented. Thus, this activity makes a positive contribution to improving digital literacy and students' understanding of the importance of operating systems in everyday life.